2020 ACC/AHA Guideline for the Management of Patients With Valvular Heart Disease: Executive Summary. Issue 5 (2nd February 2021) - Otto, Catherine M.; Nishimura, Rick A.; Bonow, Robert O.; Carabello, Blase A.; Erwin, John P.; Gentile, Federico; Jneid, Hani; Krieger, Eric V.; Mack, Michael; McLeod, Christopher; O'Gara, Patrick T.; Rigolin, Vera H.; et al.
Abstract : Aim: This executive summary of the valvular heart disease guideline provides recommendations for clinicians to diagnose and manage valvular heart disease as well as supporting documentation to encourage their use. Methods: A comprehensive literature search was conducted from January 1, 2010, to March 1, 2020, encompassing studies, reviews, and other evidence conducted on human subjects that were published in English from PubMed, EMBASE, Cochrane, Agency for Healthcare Research and Quality Reports, and other selected database relevant to this guideline. Structure: Many recommendations from the earlier valvular heart disease guidelines have been updated with new evidence and provides newer options for diagnosis and treatment of valvular heart disease. This summary includes only the recommendations from the full guideline which focus on diagnostic work-up, the timing and choice of surgical and catheter interventions, and recommendations for medical therapy. The reader is referred to the full guideline for graphical flow charts, text, and tables with additional details about the rationale for and implementation of each recommendation, and the evidence tables detailing the data considered in developing these guidelines. Abstract : Supplemental Digital Content is available in the text.